Case Report: Next-Generation Sequencing in Diagnosis of Atypical Aspiration Pneumonia - Zhang, Quan; Xu, Wei; Peng, Fei; Lei, Si; Zhong, Yanjun; Yi, Jun; Wu, Shangjie (Frontiers in Public Health, 2022)
Since the pandemic of Corona Virus Disease 2019 (COVID-19), especially in the centers most affected, the symptoms like fever, cough, myalgia or fatigue, and radioactive signs typically related to COVID-19 like ground-glass opacity (GGO), often distract physicians’ attention from other diseases. Aspiration pneumonia and COVID-19 share similarities in some aspects. There may be risk of misdiagnosis in the case of considering radiological patterns of pneumonia only. Early diagnosis and treatment often greatly improve prognosis. We herein reported a case of 40-year-old patient who underwent chest computed tomography (CT) scan with the discovery of ground-glass opacity, intralobular reticular opacity and interlobular septal thickening, consolidation and air bronchogram sign, which were mainly located in the middle and upper lobes of the right lung. It was considered to be infection related pneumonia based on the negative reverse transcription-polymerase chain reaction (RT-PCR) result of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The next-generation sequencing (NGS) of bronchoalveolar lavage fluid (BALF) was performed and detected nucleic acid sequences of Klebsiella sp.. Consequently, the patient accepted sensitive intravenous antibiotics therapy for thirteen days and had a remarkable clinical and radiological improvement. His case was followed up through imaging procedures. Because of possible radiologic and clinical similarities between aspiration and COVID-19 pneumonia, COVID-19 can be of some value in proposing a differential diagnosis of aspiration pneumonia. Clinicians could suggest a correct diagnosis by careful examination of the CT images together with attention to the clinical history and judicious utilization of NGS, especially.